Nigerian Libraries and Information Literacy in the 21St Century: How Far, So Far? - A. Adeleke, Akinniyi; Arikawe, Samuel; Asaolu, Aderonke (Information World, 2015)
The study examined the status of information literacy in Nigerian libraries by surveying librarians who subscribed to the Nigerian Library Association (NLA) online forum. Seventy three librarians responded to the multi-item, self-developed questionnaire designed for the study. The survey revealed that information literacy was still at the formative stage and that it was more commonly taught in academic libraries than in other types of libraries. Similarly, the study discovered that information literacy was not regularly implemented in the libraries. Stemming from the findings of the study, recommendations were suggested to improve the status of the programme in Nigerian libraries.
Keywords: Information literacy; Nigerian libraries; User education; Use of library; Nigeria